Brumes et brouillards de Bleak House à Heart of Darkness - Audrey Sabathier-Lepetre (Cahiers Victoriens et Edouardiens)
This article analyses the ways in which air is combined to water to generate mist or fog in three novels of the Victorian period (Bleak House, Tess of the d’Urbervilles and Heart of Darkness). In these novels, mist and fog are recurrent and deeply ambivalent tropes. The article will first raise the following question : to what extent does the representation of fog and mist take part in the representation of the « Britishness » of the place described ? It will focus on the different interpretations of these tropes by drawing comparisons between short excerpts of the novels. It will notably draw a link between mist or fog and a double process of mythification and mystification. It concludes by suggesting that, being signifiers of blurriness, the mists and fogs depicted in the novels are characterised by the unstable or drifting quality of their meaning.